"Think it. Mix it. Vape it.": A Content Analysis on E-Cigarette Radio Advertisements. (3rd July 2019) - Nicksic, Nicole E.; Brosnan, Phoebe G.; Chowdhury, Nadia; Barnes, Andrew J.; Cobb, Caroline O.
Abstract: Background: E-cigarette (EC) use is increasing rapidly across the United States, especially among youth. EC advertisements are one likely contributor to this increase, as they currently have few marketing restrictions. Radio advertising reaches most of the U.S. population and may be particularly influential in this regard. Objectives: The purpose of the current study was to examine content themes and spending data from EC radio advertisements. Methods : Competitrack, a marketing tracking firm, gathered 19 advertisements from four different EC brands across the United States from 2015 to 2016, which were coded by two individuals and analyzed for main content themes. Additionally, spending data were analyzed by identified EC brand. Results: Logic was the most common EC brand advertised on the radio and included themes potentially appealing to youth, such as humor and sound effects. Of the 28 analyzed content themes, references to "taste" were the most popular, followed by highlighting benefits of using ECs, presence of music, and comparison to other EC brands. Only Logic advertisements ( n  = 7) included health disclaimers and age restriction messages, yet frequently included themes that were attractive to youth. Conclusions/Importance: As these radio advertisements are exposing youth and other vulnerable populations to ECs, regulations, similar to those made for conventional cigarette advertising, are necessary for prevention efforts.